Site Logistics Factors Impacting Resource Use on Construction Sites: A Delphi Study - Dixit, Manish Kumar; Venkatraj, Varusha; Pariafsai, Fatemeh; Bullen, Jason (Frontiers in Built Environment, 2022)
Over 48% of the world’s energy is consumed by buildings in their construction and operation alone, which add to over 39% of global carbon emissions. In addition, the building sector generates over 569 million tons of waste every year within just the United States. Reducing the environmental impacts and construction waste generated by buildings has, therefore, become a concerning global issue. Very few studies have addressed how site logistics planning may impact construction resource use on a site and how it may affect a project’s embodied energy. Site logistics plans control the sequencing of labor, materials, and equipment. Inefficient plans may lead to rework, material damage, and waste generation, requiring additional materials to complete the same task, which eventually increases the embodied energy of a project. In this study, we investigated, identified, and ranked site logistics-related factors that may affect the amount of resources used in a construction project. The Delphi Method is applied to determine, verify, and rank these factors to help improve existing methods of site logistics planning from an embodied energy perspective. Results show that the installer’s skill, technology/equipment, prefabrication, planning and forecasting, and material movement are among the top influential site logistics-related factors that may help reduce construction waste. Considering these factors while developing the site logistics plan will help lower the energy and carbon footprint of a construction project.